2003
DOI: 10.1520/jfs2000381
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Initial Evaluation of 1,2-Indandione as a Reagent for Fingerprint Detection

Abstract: 1,2-Indandione has been used to develop fluorescent fingerprints on porous materials such as paper. The compound reacts with amino acid residues to produce highly fluorescent fingerprint ridges. An optimized formulation and treatment protocol for using the reagent is presented here. The reagent is applied as a solution in HFE7100 containing acetic acid and ethyl acetate. Treated articles are heated at 100°C for 10 min at ambient humidity and stored in the dark before recording the fingerprints u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…4) was proposed as a fingermark reagent in 1997 by Ramotowski et al [3] following research into ninhydrin analogues by Jouille and co-workers, in conjunction with the US Secret Service. Following this discovery researchers in Australia [4], Israel [5,6], the USA [7,8], the United Kingdom [9,10] and Canada [11] have conducted research into the capabilities of 1,2-indanedione as a fingermark reagent.…”
Section: 2-indanedionementioning
confidence: 99%
See 3 more Smart Citations
“…4) was proposed as a fingermark reagent in 1997 by Ramotowski et al [3] following research into ninhydrin analogues by Jouille and co-workers, in conjunction with the US Secret Service. Following this discovery researchers in Australia [4], Israel [5,6], the USA [7,8], the United Kingdom [9,10] and Canada [11] have conducted research into the capabilities of 1,2-indanedione as a fingermark reagent.…”
Section: 2-indanedionementioning
confidence: 99%
“…This could perhaps be attributed to the substantially lower concentration of the 1,2-indanedione formulations used by the UK HODSB. Research by the HOSDB gave an optimum formulation of 0.025% w/v whereas all other research performed have been based on formulations ranging from 0.05 to 0.3% w/v [10].…”
Section: 2-indanedionementioning
confidence: 99%
See 2 more Smart Citations
“…The fluorescence of some of the compounds evaluated was found to be superior to that of DFO even without subsequent zinc salt treatment. Other studies found that the performance of DFO was superior to Ind (12)(13)(14). Another publication reported that when deciding with which reagent to process porous items (ninhydrin or 1,2-indanedione), the latter would be the primary choice (15).…”
mentioning
confidence: 91%